Mental health and wellbeing of Indonesian medical students: A regional comparison study. (September 2022) - Kloping, Nabila Ananda; Citraningtyas, Theresia; Lili, Rossalina; Farrell, Sarah Marie; Molodynski, Andrew
Background: Our previous research found very high levels of burnout and mental health problems among medical students across Indonesia, in line with rates in many other countries. This study further analyses the data by comparing six different regions of Indonesia to determine any differences between them on such measures and to look for possible explanations. Results: Our sample of 1, 729 students reported high levels of burnout and 'mild' psychiatric illness across all six regions. There were however significant differences between some regions. Sumatran students reported the lowest scores for both the Oldenburg Burnout Inventory (OLBI) and General Health Questionnaire 12 (GHQ12) scales. Sources of stress also varied among regions, with relationships and study the most reported. Further exploration of possible cultural differences is needed as well as prompt mental health support for medical students.